Training of junior rowers before world championships. Effects on performance, mood state and selected hormonal and metabolic responses - Steinacker, J. M.; Lormes, W.; Kellmann, M.; Liu, Y.; Reissnecker, S.; Opitz-Gress, A.; Baller, B.; Gunther, K.; Petersen, K. G.; Kallus, K. W.; Lehmann, M.; Altenburg, D. (The Journal of Sports Medicine and Physical Fitness, 2000)
Few data have been published on training of competitive athletes and about metabolic, hormonal and psychological reactions to overreaching (transient over-training) and tapering in successful athletes. METHODS: Training was recorded and effects on mood state and metabolic and hormonal responses were examined in 10 rowers and spares of the coxed eight during preparation for the World Championships 1995. Mood state was determined using the Recovery-Stress-Questionnaire for Athletes. Resting morning blood parameters as well as performance were measured every week over a period of five weeks. RESULTS: Very high training loads of approximately 3.2 hours per day were sustained for 18 days. Maximum performance (Pmax) and maximum lactate (Lamax) were decreased during high-load training phases (overreaching), Pmax, Lamax and endurance increased after the tapering period. There were decreases in gonadal and hypothalamic steroid hormones (fsh, 1h, prolactin, testosterone) during overreaching and increases in these hormones in tapering. Both performance and hormonal indices of training load were reflected by deterioration of recovery in the Recovery-Stress-Questionnaire for Athletes. CONCLUSIONS: Clear signs of overreaching were found after 18 days of intense training of about 3 h.d(-1) in these highly-trained athletes, i.e. decreases in performance, gonadal and hypothalamic steroid hormones and deterioration of recovery in the psychological questionnaire. After tapering values returned to baseline values before the World Championship. The findings indicate that overreaching is an integral part of successful training regimens and can be analyzed by a multi-factorial approach involving biological and psychometric data.